The prospective of introducing Islamic banking system in Tajikistan: using theory diffusion and innovation (TDI) approach - Ashurov, Sharofiddin; Bin Idris, Ahmed Fauzi; Abdullah Othman, Anwar Hasan (International Journal of Economics, Commerce and Management, 2018)
Tajikistan is a majority Muslim country located in Central Asia where Islamic finance has yet to be established. However, given the challenges of current banking practices in the country and the on-going ill effects of the financial crisis, the authorities are looking for solutions to rectify the unproductive banking and financial system in the country. Accordingly, the purpose of this research is to investigate the prospects of introducing an Islamic banking system in Tajikistan through analyzing intention towards the adoption of Islamic banking by using a quantitative approach. Besides that, the study also examines the mediating effect of perceived trust in the relationship between the relative advantage, awareness, product knowledge, social norm and adoption of Islamic bank in the country. The quantitative data is collected through questionnaire administered to 408 respondents in Dushanbe, Khujand and Qurghonteppa in Tajikistan. A measurement and structural model was formulated and estimated through adopting the structural equation modeling approach (using AMOS version 22.00). One of the major findings of this study is that the people in Tajikistan know generally about adoption of an Islamic bank, but do not have much specific product knowledge, relative advantage, and perceived trust in adoption of Islamic banking. Another significant outcomes of this study showed that the perceived trust has partial mediator effect between awareness, product knowledge, relative advantage, social norm and adoption of Islamic bank. The possible implication is to provide useful gaudiness for Policy makers to establish and develop the Islamic banking system in Tajikistan, since the results of the study provide them with all the necessary relevant information that the current conventional banking system are facing, and based on these weakness of the Current Banking system, the Islamic banking system should be proposed to solve and remedy the Banking difficulties and challenges in the country to have sustainable economic growth.